Numerical and Experimental Analysis of the Potential Fuel Savings and Reduction in CO Emissions by Implementing Cylinder Bore Coating Materials Applied to Diesel Engines (2021)
Currently, internal combustion engines contribute to the problem of global warming due to their need to use products derived from fossil resources. To mitigate the above problem, this study proposes the use of coatings on the cylinder bore in order to reduce fuel consumption and polluting emissions. Therefore, in the present study a numerical model is developed in which the tribological behavior, heat fluxes, and leakage of the combustion gases in the chamber are considered to evaluate the influence of the coating. Nickel nanocomposite (NNC) and diamond-like carbon (DLC) coatings are considered in the study. The results demonstrate that the NNC coating produces a 32% reduction in the total friction force of the compression ring. The estimated maximum temperatures for the lubricating oil were 214, 202, and 194 ◦C for the DLC, steel, and NNC materials. Increasing the temperature in the DLC coating can cause a reduction in the tribological performance of the lubricant. The estimates made show that the implementation of the NNC coating allows a maximum reduction of 5.28 ton of fuel and 39.30 kg of CO emissions, which are based on the global fleet of diesel engines forecast for the year 2025 (corresponding to one hundred and eighty million engines) and a test time of 1800 s. The proposed numerical model allows future analyses to be carried out for other types of materials used as coatings. Additionally, the model can be expanded and adapted to consider other systems that involve friction processes in the engine.